Pengaruh Gaya Kepemimpinan Path–Goal terhadap Keberhasilan Proyek melalui Komunikasi dengan Manajemen Konflik sebagai Variabel Moderasi - Muchammad Lukman Affandi; Romauli Nainggolan (Journal of Economics and Management Scienties, 2026)
This study examines the effect of Path–Goal leadership on construction project success through communication, with conflict management as a moderating variable. The study was conducted at PT Sirajasa Bentalatama, a construction services company, focusing on projects characterized by high time pressure, cross-functional coordination, and relatively lean team structures. A quantitative explanatory approach was employed, with data collected from 162 operational-level project personnel and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that Path–Goal leadership has a significant direct effect on project success and a significant effect on project communication. Communication also has a significant effect on project success and partially mediates the relationship between Path–Goal leadership and project success, indicating that leadership influences project outcomes both directly and indirectly through improved communication. Furthermore, conflict management significantly moderates the relationship between Path–Goal leadership and project success, but does not moderate the relationship between Path–Goal leadership and communication. These findings highlight that construction project success is not solely determined by technical and planning aspects, but is strongly influenced by the active role of the Project Manager in directing work, fostering effective project communication, and managing conflict constructively, particularly in projects with relatively lean organizational structures.